Pum Pum Rule Jamaican Dance: An Analytic Response to the Inability to Recognize Female Sovereignty in Dancehall - Leslie-Ann Fullerton (Caribbean Studies Students' Union, 2015)
"Pum Pum Rule Jamaican Dance: An Analytic Response to the Inability to Recognize Female Sovereignty in Dancehall" by Leslie-Ann Fullerton